PENGOLAHAN AIR LIMBAH BUDIDAYA PERIKANAN MELALUI PROSES ANAEROB MENGGUNAKAN BANTUAN MATERIAL BAMBU - Febrianto, Johannes; J. Purwanto, M. Yanuar; B. Waspodo, Roh S (Departemen Teknik Sipil dan Lingkungan IPB, 2016)
The aim of this research was to study the effectivity of bacterium in a simple anaerobic wastewater treatment reactor for degradating the pollutans. The configuration of the reactor used cylindrical plastic material with capacity of 150 L. Meanwhile, the supporting media that used as fixed bed reactor was bamboo with length 23-25 cm, width 3-4 cm, and thickness 0.5 cm. The surface area was 30 m2/m3, 40 m2/m3, and 50 m2/m3 that put into each bioreactor. The biofilm formed in bioreactor and fixed bed medium after cultivating during 30 days. By using the surface area of 50 m2/m3, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and ammonia dropped in aquaculture wastewater. The efeciency of BOD5 COD, and ammonia in sampling period test of seven days were 82.28%, 23.08%, and 46.95%, respectively.